Assessment Of Prevalence And Outcomes Of Common Infections And Physicians’ Perception Towards Antimicrobial Prescribing Among Geriatric Patients In Penang, Malaysia - Akhtar, Ali (2022)
Geriatrics are susceptible to infections, especially respiratory tract infections, urinary tract infections and skin infections due to their compromised immune system. Moreover, unnecessary antimicrobial use is an emerging problem throughout the world. The main objectives of current research project are to assess the prevalence and outcomes of respiratory tract infections, urinary tract infections and skin infections among the geriatric patients, along with the perceptions of physicians working at public hospital about antimicrobial use and resistance. A cross-sectional study was conducted at three departments (respiratory, urology, dermatology) of Hospital Pulau Pinang, Malaysia. Patients aged ≥ 65 years with confirmed diagnosis of respiratory tract infections, urinary tract infections and skin infections with their complete medical records were included in the study. The most prevalent respiratory tract infection was community acquired pneumonia (65.6%) followed by chronic obstructive pulmonary disease (20.7%), bronchitis (8.2%) and hospital-acquired pneumonia (5.5%). Smoking (OR = 0.383 [95% CI: 0.186-0.787]; p = 0.009), alcohol consumption (OR = 0.583 [95% CI: 0.357-0.951]; p = 0.031), polypharmacy (OR = 1.858 [95% CI: 1.245-2.774] ; p = 0.002) and presence of other co-morbidities (OR = 0.643 [95% CI: 0.429-0.964]; p = 0.032) are statistically significant factors associated with treatment outcomes of respiratory tract infections among geriatrics.